PENGARUH PROBLEM BASED LEARNING BERBANTUAN KAHOOT TERHADAP NUMERASI SISWA - Mukti, Trisna; Yustitia, Via (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study found that fifth-grade elementary school students have low numeracy skills due to the lack of use of models and learning media. To address this issue, the Problem Based Learning model assisted by Kahoot was used. This study aims to evaluate the effects of the model on students' numeracy skills and the activity of using Kahoot. The methodology used is Quasi-Experimental quantitative research with a Posttest-Only Control Group design. The research population consists of fifthgrade students at Hang Tuah 10 Juanda Elementary School, with a sample of all students from classes V-A and V-D totaling 42 students, selected using the Cluster Random Sampling technique. Information was collected through tests and observations, using test sheets and student activity observation sheets as instruments. Data processing involves normality tests, homogeneity tests, and hypothesis tests (T-test). The results of the T-test show that Problem Based Learning assisted by Kahoot significantly improves students' numeracy skills. In addition, observations show that students are actively engaged in various learning activities in the classroom. It is concluded that the use of Kahoot as a learning medium has a positive impact on the improvement of students' numeracy skills.